Observasi Observing The Performance of Gogo Rice Breeding Lines - Angelita Puji Lestari; Tomy Arianto; Sukirman Sukirman; Rini Hermanasari; Yullianida Yullianida; Oma Oma; Djajuli Gafur; Ade Suhaeri; Anggiani Nasution; Santoso Santoso; Aris Hairmansis (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Observation is one of the stages in the selection to obtain the expected rice lines to be tested at the yield and multi-location testing stage as candidates for breeding rice varieties. The research was carried out at the Tamanbogo Lampung Experimental Garden in the 2021 planting season (MT) using an augmented design with five replications of comparison varieties: Inpago 8. Inpago 12, Inpago 13. Situbagendit, and Situpatenggang. As many as 247 promising breeding rice lines were used as materials in this experiment with their respective advantages. Each line was planted with a 0.9 m x 5 m plot size with a spacing of 30 cm x 15 cm. Fertilizer used is 300 kg/ha NPK + 100 kg/ha Urea. Weeding is done twice, precisely at the time before the next fertilization I and II. The observations include 50% flowering age, harvest age, plant height, tiller quantity, dry-milled grain yield, and resistance to biotic and abiotic stresses. The analysis of variance showed that the genotype significantly affected plant height and productive tiller quantities. High heritability and genetic advances in plant height characters indicate that this character is a selection criterion so that selection can be made to increase these characters. The comparison varieties significantly affected the character of plant height and productive tiller quantities. From this activity, 37 breeding lines were obtained with higher yields than the comparison varieties.